Study and Investigate Strength and Durability of Concrete Replaced with Silica Fume and Fly Ash - Kumar, Ashok; Jain, Neeraj (International Journal of Scientific Research in Civil Engineering, 2022)
The last few decades are well thought-out to be the era of the self-compacting concrete and thousands of researches has been carried out. In India, the development of concrete possessing self-compacting properties is still very much in its initial stages. Over the past couple of years, few attempts were made still the cost of production of such concrete is a challenging issue for the present concrete engineers. Hence, in the present study an attempt is done to understand the effect of copper slag as a mineral admixture on the properties of self compacting concrete. Hence, our attempt is to produce more economical, durable and sustainable SCC using mineral admixture. Basically the Fly Ash and Silica Fumes are industrial by-products. In this study, the optimal percentage of these by-products for partial replacement of cement is studied in respect of their resulting concrete’s strength properties. For fly-ash, 5%, 10%, 15%, 20%, 25%, 30% and 35%, of replacement is tried and for silica fume, 0%, 4%, 6%, 8%, and 10%, of replacement is tried to arrive at their optimal replacement to get the desired strength and durability properties of the concrete. Compressive strengths were tested on cubes, split tensile strengths were tested on cylinders and flexural strengths were tested on beams. The specimen’s durability properties were tested with sulphate and acid attacks.
Keywords: Self Compacting Concrete; Admixture; Silica Fume; Fly Ash; Durability Test; Strength Test